2015
DOI: 10.1093/hmg/ddv462
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing of over 4100 men of African ancestry and prostate cancer risk

Abstract: Prostate cancer is the most common non-skin cancer in males, with a ∼1.5-2-fold higher incidence in African American men when compared with whites. Epidemiologic evidence supports a large heritable contribution to prostate cancer, with over 100 susceptibility loci identified to date that can explain ∼33% of the familial risk. To explore the contribution of both rare and common variation in coding regions to prostate cancer risk, we sequenced the exomes of 2165 prostate cancer cases and 2034 controls of African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
(65 reference statements)
0
25
0
Order By: Relevance
“…Our study suggests that there are still unexplained reasons for the aggressive nature of prostate cancer in AA men that is only partially explained by the genomic studies to date. Additional studies focused on metastatic CRPC samples from AA men and development of methodologies to integrate analyses of somatic and germline data may improve our understanding of the nature of aggressive prostate cancer in these patients (23,4547). Our results suggest that inclusion of sufficient numbers of patients of African ancestry in cancer genomic studies may enable the discovery of new cancer genes and inform the inclusion of diverse populations towards precision cancer medicine (48).…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that there are still unexplained reasons for the aggressive nature of prostate cancer in AA men that is only partially explained by the genomic studies to date. Additional studies focused on metastatic CRPC samples from AA men and development of methodologies to integrate analyses of somatic and germline data may improve our understanding of the nature of aggressive prostate cancer in these patients (23,4547). Our results suggest that inclusion of sufficient numbers of patients of African ancestry in cancer genomic studies may enable the discovery of new cancer genes and inform the inclusion of diverse populations towards precision cancer medicine (48).…”
Section: Discussionmentioning
confidence: 99%
“…Because 22Rv1 was derived from a xenograft of CWR22R cells which was serially propagated in mice, it would be appropriate to also assign this mixed ancestral racial classification to the CWR22R cell line. The implications of 22Rv1 and CWR22R carrying AFR genetic ancestry are far reaching as genetic factors associated with AFR ancestry have been recently linked to prostate tumor aggressive properties . Further studies are needed to determine if these cell lines carry any of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided compelling evidence in support of the notion that PCa health disparities result from the interplay of multiple factors, including biological/genetic factors . For instance, several recent studies have reported genomic differences between AA men with PCa and Caucasian or European American (EA) with PCa, suggesting a potential role for biological mediators in driving PCa mortality disparities . Understanding how these mediators contribute to increased PCa mortality in AA men requires mechanistic functional studies in pre‐clinical cellular and animal models of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…To date, to the best of our knowledge, four reported GWAS studies have been conducted with a primary focus on MAA from 2007–2016, as 10% of all GWAS PCa studies over the last decade. From these investigations: genetic variant/s in a number of chromosomal regions such as, 8q24 (working in conjunction with another variant) was twice more prevalent in MAA compared to MEA, a novel risk variant, rs7210100 in the 17q21 region was unique to African‐Americans, while its functionality is unknown with respect to PCa, it is reported to be associated to the breast cancer susceptibility gene, BRAC1; a risk variant in 10p14 was most prevalent in Ghanaian men while sub‐analysis associated SNPs at 5q31.3 with high Gleason score and finally, Rand et al reported PCa associations to the gene SPARCL1 on 4q22.1 and PTPRR on 12q15.…”
Section: Causes For Prostate Cancer Disparitiesmentioning
confidence: 99%